Increasing Global Awareness through Professional Learning Community: A Study from LATTICE - Dion Efrijum Ginanto (Universitas Jambi, Magister Program of English Education Department, 2018)
Using three components of PLCs by DuFour (2004), I explored the learning communities at LATTICE (Linking All Types of Teachers to International, Cross-cultural Education). DuFour (2004) argued that PLCs is a form of learning communities held at the school level to improve the school quality. It means PLCs happen in the school context. However, Easton (2011) contended that learning community could happen inside or outside schools. This paper intends to analyze a learning community at LATTICE in creating more global perspective teachers. The study found that PLC s can also occur outside schools by including participants other than teachers. Based on the interviews and observations analysis, this study found that LATTICE did reflect PLCs and significantly helped K-12 educators foster their global understanding.